Aptamer-based fluorescence biosensor for chloramphenicol determination using upconversion nanoparticles. (April 2015) - Wu, Shijia; Zhang, Hui; Shi, Zhao; Duan, Nuo; Fang, CongCong; Dai, Shaoliang; Wang, Zhouping
Abstract: A novel aptamer-based fluorescence biosensor was developed for the detection of chloramphenicol (CAP) using aptamer-conjugated magnetic nanoparticles (MNPs) for both recognition and concentration elements and using upconversion nanoparticles (UCNPs) as highly sensitive signal labels. The bioassay system was fabricated by immobilizing aptamer onto the surface of MNPs, which were employed to capture and concentrate CAP. In the absence of target, MNPs-aptamer hybridizes to its complementary DNA (cDNA) which was modified with UCNPs, form the duplex structure therefore giving a maximum fluorescent signal. Upon CAP addition, the aptamer preferentially bound with CAP and caused the dissociation of some cDNA, liberating some UCNPs-cDNA and leading to a decreased fluorescent signal on the surface of MNPs. Under optimized assay conditions, a wide linear detection range (from 0.01 to 1 ng mL −1 ) was achieved with a detection limit down to 0.01 ng mL −1 . The proposed method then was successfully applied to measure CAP in contaminated milk samples and validated by a commercially available enzyme-linked immunosorbent assay (ELISA) method. Improved by the magnetic separation and concentration effect of MNPs, the high sensitivity of UCNPs and the high affinity of aptamers, the present method performs with both high sensitivity and selectivity for CAP. Besides, this strategy can be applied to detect other antibiotics. Utilization of the proposed biosensor for quantitative determination of antibiotics in food samples may provide significant improvements in quality control of food safety. Highlights: An aptamer-based fluorescence biosensor was developed for CAP detection. Upconversion nanoparticles were used as highly sensitive signal labels. Aptamer-conjugated MNPs were used for both recognition and concentration elements. The sensor design is general and can be applied to other aptamer-based sensors.